Challenges and strategies of all-inorganic lead-free halide perovskite solar cells. Issue 5 (1st March 2022) - Wei, Huiyun; Qiu, Peng; Li, Ye; He, Yingfeng; Peng, Mingzeng; Zheng, Xinhe; Liu, Xiaohu
Abstract: Hybrid lead halide perovskite solar cells (PSCs) have experienced a rapid development in the past decade and a certified efficiency up to 25.5% has been achieved. However, the presence of toxic lead component and the inherent poor thermal stability of the organic cations in the hybrid lead halide perovskites obstruct the commercial applications of their corresponding photovoltaic devices. Therefore, fabricating high-efficient all-inorganic lead-free PSCs is a promising direction. This review summarizes the related research progress, which mainly focuses on the structural and optoelectronic properties of inorganic lead-free perovskites and devices. In particular, the strategies for improving the properties and stability of Cs–Sn perovskites, as well as enhancing the photovoltaic performance of the corresponding devices are highlighted. An outlook of challenges and future directions regarding to all-inorganic lead-free PSCs are also proposed.